Kajian Maskulinitas dan Masa Depan Kajian Gender dan Pembangunan di Indonesia - Nur Hasyim (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2017)
This paper argues that men and masculinity studies influence the direction of gender studies and development in Indonesia. Through literature review and participatory observation, the author as a male activist that engage in advocating gender justice and gender based violence prevention for more that fiveteen years presents five indications that support the thesis. Among those indications are; first, the growing of men and masculinity studies in Indonesia. Second, transformation of Pusat Studi Wanita (Center for Women Studies) into Pusat Studi Gender dan Anak (Center for Research on Gender and Children). Third, the growing of men movement for gender justice. Forth, the growing of research on men and masculinity in Muslim society. This paper also argues that study on masculinity and Islam is challenging field since very few scholars who explored this issue. Moreover this paper points out that research on masculinity and Islam will contribute to the development of global discourse on masculinity.